Estrutura eletrônica de derivados de politieno[3,4-b]-tiofeno-co-benzoditiofeno para aplicação em camadas ativas de células solares orgânicas - Roldao, Juan Carlos (2016)
Currently there is an intensive search for new materials with tuned properties for use in organic solar cells to obtain an increase in its conversion efficiency and replace silicon devices. The polythieno[3,4-b]-thiophene-co-benzodithiophene (PTB7) is a polymer recently proposed in the literature and with very interesting properties in organic solar cells, which places it as a possible alternative to the widely used poli(3-hexilthiophene) (P3HT). It has been reported changes in different positions of the monomeric unit of this copolymer, both in benzodithiophene (BDT) structure, as in the thienothiophene (TT) structure that compose it. These modifications led to new polymers with different properties and sometimes more interesting than those of PTB7 without substitutions. The work to be presented aimed to study the structural, electronic and optical properties of PTB7 and possible changes due to chemical changes made in the BDT structure of its monomeric units. This study employed optimization tools like Molecular Mechanics, Molecular Dynamics and Parametric Method 6 (PM6), as well as calculations of the electronic structures with the Density Functional Theory (DFT) method, and optical properties such as the Time Dependent Density Functional Theory (TD-DFT) calculations. We conclude that the PTB7 chains in the solid state can be considered planar. With our model for PTB7, we obtained a difference ΔEHL between the Highest Occupied Molecular Orbital (HOMO) and the Lowest Unoccupied Molecular Orbital (LUMO) of approximately 1.84 eV, and this value is in good agreement with the experimental value. Regarding chemical substitutions, we studied theoretically 8 derivatives of PTB7 and the results showed that it is possible to obtain compounds with a significant decrease in ΔEHL and that it is possible to obtain compounds with HOMO and LUMO energy values more adjusted to the widely employed acceptor material phenylC61-butyric acid methyl ester (PCBM).